Peran Mural dalam Membangun Identitas Arsitektur Kota - Rifany Syahrizal Oktavian; Fuad Nasim Hamid (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
The important role of murals in building the architectural and visual identity of a city. Murals have become an integral part of public spaces in many cities, not only as beautiful works of art, but also as a medium to convey social, cultural and political messages. In the urban context, murals play a key role in building the image and character of a city, especially by utilizing open spaces that are often not optimally utilized. The identity of a city is not only determined by its buildings and physical infrastructure, but also by how people interact with the space around them, and murals are an important element in this process. With a deep understanding of the history, aesthetics and symbolism of murals, we can see how this medium can be utilized to create a more vibrant, meaningful urban environment that reflects local identity. This topic is very interesting and important in the context of current urban development, and this abstract provides an overview of the initial focus of research that will explore the findings and apply relevant practices.